2007
DOI: 10.4049/jimmunol.178.3.1938
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated ERM Is Responsible for Increased T Cell Polarization, Adhesion, and Migration in Patients with Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune/inflammatory disease characterized by autoantibody production and abnormal T cells that infiltrate tissues through not well-known mechanisms. We report that SLE T lymphocytes display increased levels of CD44, ezrin, radixin, and moesin (ERM) phosphorylation, stronger actin polymerization, higher polar cap formation, and enhanced adhesion and chemotactic migration compared with T cells from patients with rheumatoid arthritis and normal individuals. Silencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
160
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 29 publications
10
160
0
Order By: Relevance
“…Rho-associated kinase (ROCK)2 was shown recently to be implicated in the regulation of autoimmunity in mice and humans (13)(14)(15). Previous findings demonstrated that oral administration of a selective ROCK2 inhibitor (KD025) in healthy subjects decreases IL-17 and IL-21 secretion induced by ex vivo stimulation (15 immunosuppressive T cell subsets via concurrent regulation of STAT3/STAT5 phosphorylation (16)(17)(18).…”
mentioning
confidence: 99%
“…Rho-associated kinase (ROCK)2 was shown recently to be implicated in the regulation of autoimmunity in mice and humans (13)(14)(15). Previous findings demonstrated that oral administration of a selective ROCK2 inhibitor (KD025) in healthy subjects decreases IL-17 and IL-21 secretion induced by ex vivo stimulation (15 immunosuppressive T cell subsets via concurrent regulation of STAT3/STAT5 phosphorylation (16)(17)(18).…”
mentioning
confidence: 99%
“…For example, three different roles have been reported for the involvement of ezrin-moesin in immunological synapse (IS) formation: ERM was found to be essential for the assembly of IS and the recruitment of ZAP70 in one group of studies (Roumier et al, 2001;Ilani et al, 2007); ezrin was reported to be completely dispensable for IS formation in another study (Shaffer et al, 2009); and in yet a third proposal, ezrin was also declared to negatively regulate IS formation (Faure et al, 2004). Similarly, opposite effects of ERM have been documented for T-lymphocyte movement; T-cell migration could be enhanced by either ERM phosphorylation (Li et al, 2007) or ERM dephosphorylation (Brown et al, 2003). The negative effect of ezrin in Fas-induced apoptosis presented in this study, in contrast to the previously reported positive role for ezrin, highlights another controversy that is centered on the membrane events involving ERM.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the former findings was highlighted by the demonstration that in kidney biopsies from patients with lupus glomerulonephritis, infiltrating T cells expressed CD44 and pERM. In contrast, biopsies from allografts undergoing rejection displayed CD44+ T cells, but lacked pERM expression [14].…”
Section: Cd44 and Permmentioning
confidence: 89%
“…Hence, treatment of SLE T cells with Y27632, a specific inhibitor of Rho kinase (the enzyme that phosphorylates ERM), disrupts the formation of polar caps and hampers the increased adhesion capacity characteristic of SLE T cells. Addition of cytochalasin D (an actin polymerization inhibitor) or CD44 knockdown (by RNA interference) have shown comparable effects [14]. The importance of the former findings was highlighted by the demonstration that in kidney biopsies from patients with lupus glomerulonephritis, infiltrating T cells expressed CD44 and pERM.…”
Section: Cd44 and Permmentioning
confidence: 99%
See 1 more Smart Citation